Range-wide Distribution Survey, Habitat Modeling, and Characterization of Conservation Threats to the Colombian Black Spider Monkey (Ateles fusciceps rufiventris) in Colombia: Range-wide distribution survey, habitat modeling, and characterization of conservation threats to the Colombian black spider monkey (Ateles fusciceps rufiventris) in Colombia - Hernández-Jaramillo, Alma; Shanee, Sam; Serio-Silva, Juan Carlos (International journal of primatology, 2025)
Knowledge of the geographic distributions of species is fundamental for conservation management. Ateles fusciceps rufiventris is currently listed as Vulnerable. It is found in Colombia and Panamá and may be present in Ecuador. It has been subject to very few studies and its true current conservation status is unknown. We used 3 years of interviews and field observations to determine its current distribution in Colombia, complemented with searches of the literature and databases for the entire range. We evaluated the quality of available habitat using a publicly available data layer of forest integrity information and niche modeling. We estimated the original and current extent of occurrence (EOO) of the taxon based on an ecological niche model (ENM) using MaxEnt and calculated the area of occupancy (AOO) for Colombia, where we conducted field sampling. We also identified the main threats to the subspecies during our interviews and field observations. Of the 39 sites we visited, we confirmed the presence of A. f. rufiventris by direct observation or secondary information at 15 (38%), although all sites had potential habitat for the subspecies. We estimated that the EOO of A. f. rufiventris in Colombia covers 118,730 km 2 and that forests in the potential habitat have reduced by ~ 60% in the last 30 years, leaving an estimated current AOO in Colombia of ~ 17,800 km 2 to ~ 47,000 km 2 , with just 11% in state-protected areas. Interviews and field observations showed that clearcutting for agriculture and cattle ranching were the most frequent threats at sites where we found no evidence of the subspecies. Illegal crops, hunting for subsistence and trade, including as pets, were the most frequent threats at sites where we found the subspecies. We found a dramatic reduction in suitable habitat and a high incidence of forest degradation, deforestation, and hunting affecting the subspecies. Conservation efforts should focus on restoration in strategic areas, and on reducing deforestation and hunting pressure. Community-based conservation could be employed to increase areas of protected habitat on communal lands and decrease hunting pressure, to ensure the long-term survival of this highly threatened primate.